2008
DOI: 10.1016/j.chiabu.2007.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Detection of child abuse by Dutch preventive child-healthcare doctors and nurses: Has it changed?

Abstract: This article appeared in a journal published by Elsevier. The attached copy is furnished to the author for internal non-commercial research and education use, including for instruction at the authors institution and sharing with colleagues.Other uses, including reproduction and distribution, or selling or licensing copies, or posting to personal, institutional or third party websites are prohibited.In most cases authors are permitted to post their version of the article (e.g. in Word or Tex form) to their pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 19 publications
1
18
1
Order By: Relevance
“…Reijneveld et al concluded the same in a study on trends in the rate of detection of suspected child maltreatment (3-12 years old) by CHPs. 9 At first sight, our findings contradict another previous study of the quality of diagnostic skills of CHPs. 16 Wiefferink et al 16 conducted an RCT on the effect of training CHPs to improve diagnostic competence and found an improvement on the first Table II.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…Reijneveld et al concluded the same in a study on trends in the rate of detection of suspected child maltreatment (3-12 years old) by CHPs. 9 At first sight, our findings contradict another previous study of the quality of diagnostic skills of CHPs. 16 Wiefferink et al 16 conducted an RCT on the effect of training CHPs to improve diagnostic competence and found an improvement on the first Table II.…”
Section: Discussioncontrasting
confidence: 57%
“…Thirty-four percent of the children were 5-6 years old. 9 The 3 studies used the same 2-step data collection procedure. First, PCH services were asked to participate.…”
Section: Datasetsmentioning
confidence: 99%
See 1 more Smart Citation
“…1,[7][8][9] Preventive pediatricians failed to identify psychosocial problems in approximately one-half the children whose parents reported serious problems on the Child Behavior Checklist (CBCL). 1,8 Vogels et al 10 show that the proportion of children identified as having problems varies widely between individual preventive pediatricians.…”
Section: Introductionmentioning
confidence: 99%
“…Child abuse has serious consequences at both the personal and community levels. This includes the physical and psychological consequences on the abused child (Keane & Chapman 2008, Reijneveld et al 2008). Child abuse is also associated with the likeli-hood of criminal and abusive action from these victims to society in future, such as drug addiction and violence (Thurston 2006).…”
Section: Introductionmentioning
confidence: 99%